Therapeutic Test for Differential Diagnosis of Erosive oral Lichen Planus: a Case Report - Araujo da Silva, Gabriel; Telles-Araújo, Gabriel de Toledo; Lins-Kusterer, Liliane (ARCHIVES OF HEALTH INVESTIGATION, 2024)
Oral lichen planus (OLP) is a chronic inflammatory mucocutaneous disease, mediated by T cells, whose etiology remains unknown. Clinically, OLP can also be classified into reticular, papular, atrophic, and erosive, being erosive oral lichen planus (EOLP) the second most common. The objective of this study is to report a case of EOLP submitted to a therapeutic test. A 51-year-old female patient presented with a crusted ulcerative lesion on the lower lip, bleeding to the touch, and painful symptoms, within a five-year evolution. Extraoral examination revealed an ulcerated lesion on the lower lip, erosive and erythematous areas surrounded by whitish streaks, in addition to lip dryness. On intraoral examination, an erythematous macula was noted on the left buccal mucosa, also with fine keratotic streaks on its edges. A therapeutic test was performed using systemic and topical corticosteroids. After seven days, the patient presented a satisfactory response to this approach, concluding the primary diagnostic hypothesis of EOLP. The patient remains under follow-up, with no signs of recurrence of lesions. The therapeutic test is effective when clinical characteristics are carefully observed, allowing for plausible diagnostic hypotheses.